Scrub Forest Studies-Foliar and Soil Nutrientstatus of Prosopis jullflora DC - Sharma, B. M. (Indian Forester, 1984)
A correlation of the nutrient content of the leaves with exchangeable cations in the soil for Prosopis jullflora DC. in the scrub forest of the Thar Desert of India has been presented. The soils supporting the tree are mostly yellowish brown, coarse, sandy, alkaline and having little organic carbon, nitrogen and phosphorus. Calcium and carbonates tended to increase with depth while magnesium showed a decrease. The amount of excbangeable calcium in the soil decreased mostly as the exchangeable spdium increased. In general, magnesium is comparatively higher in the habitat. Foliar analysis reveals that magnesium and phosphorus contents are less than 1 per cent but sodium Is the highest indicating the capacity of the plant to tolerate the salinity. The correlation of the soil and foliar contnmts shows that potassium and phosphorus are fairly related (r= 0.74 and 0.61 respectively).